Propranolol for management of Infantile Haemangioma: A Single Centre Experience - Singh, Nagendra; Rohit, Dushyant; Singh, Sona; Thakur, Omkar; Verma, R S (International Journal of Medical Research and Review, 2015)
Objective: Infantile hemangiomas are the most common benign tumour in infancy. Propranolol has recently been introduced as therapeutic agent for treating hemangiomas. This study explores the impact of Propranolol on hemangiomas. Study Design: Prospective study. Materials and Methods: Propranolol was given to 32 children (19 girls and 13 boys) having hemangiomas between age of 3 weeks to 12 months at a dose of 2 mg/kg per day, in 2 or 3 divided doses. Total duration of study period was one year from July 2013 to June 2014. Serial photographs were taken at 4-6 weeks interval during the course of their therapy to record clinical response. Results: out of 32 patients 31 patients showed improvement in their hemangiomas by reduction in size and change in color during propranolol therapy. Results were determined as complete resolution (n- 5, 15.6%), ongoing resolution (n-26, 81.2%). No side effects of propranolol was observed in any patient. Conclusions: Propranolol appears to be a valuable and effective treatment option for infantile hemangiomas. Propranolol is likely to revolutionize the treatment of hemangiomas.